2019
DOI: 10.3389/fpsyg.2019.00715
|View full text |Cite
|
Sign up to set email alerts
|

Pain, Parental Involvement, and Oxytocin in the Neonatal Intensive Care Unit

Abstract: Preterm infants (PTI) typically experience many painful and stressful procedures or events during their first weeks of life in a neonatal intensive care unit, and these can profoundly impact subsequent brain development and function. Several protective interventions during this sensitive period stimulate the oxytocin system, reduce pain and stress, and improve brain development. This review provides an overview of the environmental risk factors experienced by PTI during hospitalization, with a focus on the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 188 publications
(211 reference statements)
1
23
0
Order By: Relevance
“…In particular, weaker intrinsic functional connectivity of the thalamocortical pathways, and the insular cortex-limbic connections was associated with poorer locomotor outcome. This finding is corroborated by prior reports demonstrating that preterm neonates exposed to early postnatal painful events showed macro- and microstructural alterations in thalamocortical projections and other cortical regions (i.e., frontal and parietal cortex) that were associated with adverse motor and cognitive neurodevelopmental outcome in the first years of life, involving also the mechanisms of anxiety and emotion regulation (Duerden et al, 2015; Tortora et al, 2015; Navarra et al, 2016; Malavolti et al, 2017; Filippa et al, 2019). Moreover, Duerden et al (2018) demonstrated that early pain exposure can influence thalamocortical pathways maturation, especially in extremely preterm born neonates, and that the thalamic volume growth during the first weeks of life correlated with cognitive and motor scores at 36 months of age.…”
Section: Discussionsupporting
confidence: 88%
“…In particular, weaker intrinsic functional connectivity of the thalamocortical pathways, and the insular cortex-limbic connections was associated with poorer locomotor outcome. This finding is corroborated by prior reports demonstrating that preterm neonates exposed to early postnatal painful events showed macro- and microstructural alterations in thalamocortical projections and other cortical regions (i.e., frontal and parietal cortex) that were associated with adverse motor and cognitive neurodevelopmental outcome in the first years of life, involving also the mechanisms of anxiety and emotion regulation (Duerden et al, 2015; Tortora et al, 2015; Navarra et al, 2016; Malavolti et al, 2017; Filippa et al, 2019). Moreover, Duerden et al (2018) demonstrated that early pain exposure can influence thalamocortical pathways maturation, especially in extremely preterm born neonates, and that the thalamic volume growth during the first weeks of life correlated with cognitive and motor scores at 36 months of age.…”
Section: Discussionsupporting
confidence: 88%
“…Previous research with recorded music stimulation with instrumental lullaby music, selected in consultation with an accredited music therapist, has shown similar effect to the current gold standard of oral sucrose [46], and the combination of music stimulation with sucrose provides better pain relief during blood sampling than when sucrose or music is used alone [46]. Recorded mother's voice has also shown similar pain alleviating effects as oral sweet solutions [47,48].…”
Section: Introductionmentioning
confidence: 95%
“…Lack of breast milk volume in the 1 st day after birth can be caused by a lack of stimulation of the hormones prolactin and oxytocin which are very instrumental in the process of producing and releasing milk. Under certain conditions, massage can be done to stimulate the oxytocin system, reduce pain and stress, and improve brain development [16].…”
Section: Discussionmentioning
confidence: 99%